Comparison of three textbooks published for 8th grade in Iceland - Halldórsdóttir, Rannveig (NOMAD Nordic Studies in Mathematics Education, 2015)
This study compares characteristics of three Icelandic mathematics textbooks for grade 8, used over a period of 25 years. The textbooks’ structure, content, attitudes to mathematics and mathematical competences were compared and portrayed in the light of official curricula. The purpose of the study is to investigate through the focal point of textbooks the implementation of new curricular policy including new topics as well as mathematical competences and attitudes to mathematics. Our findings show that the textbooks differ considerably with respect to the characteristics studied. The objectives of mathematics formulated in the national curriculum are reflected to a great extent in the most recent textbook Átta – tíu, but the widely used translated textbook, Almenn stærðfræði I, deviates in important ways from the curriculum and much more than the Talnaspegill/Hornalína books that only stayed in use for a short while.